Modernisasi Kota: Saluran Air Bersih Perpipaan di Jawa Masa Kolonial - Krisnanda Theo Primaditya (Lembaran Sejarah, 2021)
The clean water pipeline is a project initiated and designed by the Dutch East Indies government to overcome the problem of water cleanliness in urban areas in the 20th century. At that time, clean water in colonial cities was becoming increasingly scarce due to population growth, among other things. The increasing number of residents causes water pollution in urban areas to increase. The colonial government realized the impact caused by the pollution. Several disease outbreaks began to emerge and attack the city community. Efforts to construct boreholes/artesian wells do not appear to be going as expected. Therefore, the government designed a clean water pipeline construction project to drain water from springs to the colonial city. After the construction of these new facilities, colonial cities underwent significant changes, such as an increase in living standards and cultural changes in urban communities.